Pancreatic Lipase Inhibitory And Cytotoxic Potential of A Streptomyces Species Isolated From Western Ghat soil, Agumbe, Karnataka, India - TR, Prashith Kekuda (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The present study was undertaken to investigate pancreatic lipase inhibitory and cytotoxic activity of butanol extract of a Streptomyces species isolated from the western ghat soil samples of Agumbe, Karnataka, India. The isolated organism was identified on the basis of morphological, cultural and biochemical parameters. The isolate was inoculated into Starch casein broth, incubated aerobically on a rotary shaker for 7 days at 30oC. After incubation, the culture broth was extracted with butanol solvent. Pancreatic lipase inhibitory (Anti-obesity) activity of solvent extract was tested against chicken pancreatic lipase using olive oil as the substrate. Cytotoxic activity was determined in terms of lethal nature of the extract towards the brine shrimp Artemia nauplii. The inhibition of lipase by the extract was concentration dependent and an inhibition of >60% was observed at extract concentration 50mg/ml. The mortality of brine shrimp larvae by the extract was also concentration dependent. Mortality of larvae was 100% at extract concentration 1000Î¼g/ml. The LC50 of solvent extract was found to be 42.11Î¼g/ml. The present study highlighted the pancreatic lipase inhibitory and cytotoxic potential of crude solvent extract of a Streptomyces species recovered from soil. The metabolites of actinomycetes from western ghat area of Karnataka may be useful as anti-obesity and cytotoxic agents. Further studies are needed to be carried out to isolate the active and characterize the active principles present in the crude solvent extract and determine their biological activity.